P105. Does transcranial alternating current stimulation entrain posterior alpha rhythm?. Issue 8 (August 2018) - Hermann, G.; Rothkirch, I.; Laufs, H.; Witt, K.
Abstract : Background: Previous studies described long term effects of transcranial alternating current stimulation (tACS) on alpha ( α ) frequency (Helfrich et al., 2014; Müller et al., 2015; Varlet et al., 2017).tACS was hence proposed as a tool to synchronize and modulate regional biological neuronal oscillations. Objective: Our objective was to validate tACS as a suitable method effecting neuronal oscillations over a stimulated areal.This study is part of a project that investigates the clinical relevance of the stimulation as a treatment option for impulse control disorders. Methods: We applied tACS over the occipital cortex with an α frequency of 10 Hz as well as an appropriate sham stimulation.We studied 17 participants (18–30 yrs) in two separate sessions using the neuroConn DC-stimulator plus.Before and after the stimulation three minute EEG-intervals were analysed with respect to their α peak frequency and power spectral density.We segmented these intervals in 1 s epochs and applied an FFT followed by averaging using BrainVision Analyzer and MatLab.With R statistics we computed the individual α peak frequency and the corresponding power spectral density of every EEG-channel before and after stimulation.For comparison of pre and post stimulation differences we used the Wilcoxon signed-rank test as we cannot assume our data do be normally distributed. Results: Concerning all EEG-channels, we found a significant α peak frequency shift towards the stimulated frequency in the post compared to the pre stimulation condition (Wilcoxon signed-rank test W  = 18436, p  = .002).When focusing on the electrodes in vicinity of the occipital stimulation we found that the averaged individual α peak frequencies (Electrode O1) over all participants slightly approximated the stimulation frequency.Comparing the segments before and after stimulation, peak frequency changed from 9.7 ± .8 Hz pre-stim to 10.1 ± 1.1 Hz post-stim.When analysing the individual frequency shifts to the stimulation frequency of 10 Hz with the Wilcoxon signed-rank test, we did not find any significant effect induced by tACS ( W  = 20.5, p  = 0.859) (Fig.1 ).Even analyzing α peak frequency shifts direction, no trend could be detected – out of 17 subjects only four had the expected α peak frequency drift towards the stimulation frequency (Table1 ). Conclusions: In contrast to previous work, the results of this study show a tACS-induced effect on individual α peak frequency only across all electrode positions, but we did not find any significant effect on an individual electrode near the stimulation site. This challenges the robustness of tAC stimulation effects on neuronal oscillations. In a next step, we will evaluate how tACS effects depend on the brain state (e.g. wakefulness).